Dipole Mode of the Precipitation Anomaly Over the Tibetan Plateau in Mid‐Autumn Associated With Tropical Pacific‐Indian Ocean Sea Surface Temperature Anomaly: Role of Convection Over the Northern Maritime Continent. Issue 20 (14th October 2021) - Zhang, Ping; Duan, Anmin
Abstract: Based on observational data and numerical simulation results with the Community Atmosphere Model (CAM4), version 4 atmospheric general circulation model (AGCM), the influence of the sea surface temperature anomaly (SSTA) of the tropical Pacific–Indian Ocean mode (PIM) on the interannual variability of the Tibetan Plateau (TP) precipitation in mid‐autumn (October) is investigated. We find that the interannual variation of the mid‐autumn TP precipitation is characterized by a dipole mode with a southeast–northwest inverse pattern, which is influenced significantly by the large‐scale circulation anomalies induced by PIM. During a positive phase of PIM, that is, positive SSTA in both the tropical central‐eastern Pacific and western Indian Ocean accompanied by negative SSTA around the Maritime Continent, a robust lower‐level anticyclonic anomaly over the South Asia region (SAAC) and an upper‐level cyclonic anomaly over subtropical Asia are generated owing to the Rossby wave response to the suppressed convective heating over the northern Maritime Continent. As a result, the southerly (northerly) anomalies on the west (east) side of the SAAC can enhance (reduce) the transportation of moisture and the ascending motion over the northwestern (southeastern) TP. Meanwhile, the southward‐shifted East Asian westerly jet can further enhance the ascending motion over the northwestern TP by stimulating secondary circulation. Correspondingly, a positive (negative) precipitation anomaly appears over the northwestern (southeastern) TP. During a negative phase of PIM, the opposite case is also true. Therefore, the suppressed convective heating over the Maritime Continent serves as a pivotal medium by which PIM affects the TP precipitation in mid‐autumn. Plain Language Summary: The precipitation over the Tibetan Plateau (TP) in mid‐autumn contributes substantially to the atmospheric heating source over the TP in October, which is a triggering factor for the abrupt transition of upper‐atmosphere circulation and the autumn/winter seasonal transition in East Asia. Data diagnosis and numerical simulations show that the tropical Pacific and Indian Ocean temperature anomaly mode (PIM) is a precursor signal for the variation of TP precipitation, characterized by a dipole mode with a southeast‐northwest inverse pattern. The suppressed convection over the northern Maritime Continent is a pivotal medium through which PIM (i.e., positive sea surface temperature anomaly [SSTA] in both the tropical central‐eastern Pacific and western Indian Ocean accompanied by negative SSTA around the Maritime Continent) affects the TP precipitation. It influences the upper‐ and lower‐level atmospheric circulation and provides favorable ascending motion and moisture conditions for the precipitation anomaly over the northwestern TP, while it is out‐of‐phase over the southeastern TP. Therefore, it is necessary to consider the tropical Pacific and Indian Oceans as a unified whole when studying their effects on circulation and precipitation over and around the TP. Key Points: Variation of October precipitation over the TP shows a distinct southeast–northwest inverse pattern The leading SSTA mode across the tropical Pacific and Indian Ocean (PIM) strongly influences the atmospheric circulation over South Asia The convection anomaly over the northern Maritime Continent acts as the medium by which PIM affects the TP precipitation